Nanoemulsão de kefirano e óleo essencial de coentro (Coriandrum sativum L.): elaboração, caracterização e aplicação em queijo - Cruz, Gizele Almada (2024)
Kefiran (KFR) is a heteropolysaccharide synthesized by lactic acid bacteria found in kefir grains. It consists of a protein and polysaccharide matrix, with the presence of a microbial consortium. This study aimed to develop and chemically characterize a nanoemulsion of kefiran and Coriandrum sativum L. essential oil for its application as a natural preservative in cheese. Kefiran was extracted from milk kefir grains using microwave heating. Its chemical and structural characterization was performed through elemental analysis, molecular weight determination by gel permeation chromatography, hydrogen nuclear magnetic resonance spectroscopy, infrared spectroscopy, scanning electron microscopy, and rheological analyses. The extracted kefiran was incorporated into a nanoemulsion combined with essential oil from coriander leaves (OEC). The hydrophilic-lipophilic balance was determined, and gas chromatography was used to identify its components. Based on the results, an experimental design was established, with KFR (0.5%, 1.0%, and 1.5%) and OEC (0.5% and 1.5%) as independent variables. The stability of the six formulations developed (NE1, NE2, NE3, NE4, NE5, and NE6) was observed over 30 days, considering parameters such as particle size (Z), polydispersity index (PDI), zeta potential (δ), centrifugal stability coefficient, and turbidity. The nanoemulsions were also evaluated for thermogravimetric properties and structural features (transmission electron microscopy). Non-clinical safety was assessed using adult zebrafish. Additionally, the nanoemulsions' action against strains of Salmonella enteritidis, Staphylococcus aureus, Escherichia coli, and Listeria monocytogenes was evaluated by determining the minimum bactericidal concentration (MBC) for application in commercial Ricotta cheese, applied directly. The results demonstrated that microwave heating extraction was feasible, yielding a polysaccharide with characteristics similar to those reported in the literature using different extraction methods. The major component of OEC was linalool (78%). Suspensions at the studied concentrations exhibited Newtonian fluid behavior. After experimental design, formulation NE2 (KFR-0.5% and OEC-1.5%) was considered the most stable during storage (Z, PDI, and δ). Microscopic imaging corroborated the average size found in the analyses, showing a circular shape. Regarding thermogravimetric properties, the nanoemulsion demonstrated greater stability than its isolated components, indicating efficient encapsulation. NE2 showed no in vivo toxicity. The nanoemulsion exhibited bactericidal activity against S. aureus and L. monocytogenes strains, with an MBC of 25%, which was applied to Ricotta cheese, reducing microbial load compared to the control. Thus, the proposed system, incorporating bioactives from natural sources, presents antimicrobial potential with no toxicity. Furthermore, it demonstrates good stability for application in industrialized foods, such as cheeses, with the bioactive compounds exhibiting better solubility and greater stability during production and storage.